2016
DOI: 10.1364/ao.55.002109
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of long-term evolution radio transmissions over dual-polarization combined fiber and free-space optics optical infrastructures

Abstract: This paper describes the experimental verification of the utilization of long-term evolution radio over fiber (RoF) and radio over free space optics (RoFSO) systems using dual-polarization signals for cloud radio access network applications determining the specific utilization limits. A number of free space optics configurations are proposed and investigated under different atmospheric turbulence regimes in order to recommend the best setup configuration. We show that the performance of the proposed link, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Moreover, it is very challenging and costly to overcome the last mile by fiber especially in dense urban areas. However, it can be effectively solved by the concept of Radio over Free space optics (RoFSO), which was experimentally investigated together with dual polarization RoF technology in [12].…”
Section: Analyses Of Dual Polarization Wdm and Scm Radio Over Fiber And Radio Over Fso For C-ran Architecturementioning
confidence: 99%
“…Moreover, it is very challenging and costly to overcome the last mile by fiber especially in dense urban areas. However, it can be effectively solved by the concept of Radio over Free space optics (RoFSO), which was experimentally investigated together with dual polarization RoF technology in [12].…”
Section: Analyses Of Dual Polarization Wdm and Scm Radio Over Fiber And Radio Over Fso For C-ran Architecturementioning
confidence: 99%
“…The transmission of radio signals over free-space optics (FSO), so-called RoFSO [16], offers typical flexibility of wireless communications and speed of light transmission [17]. It also provides a higher level of coverage and mobility while exploiting unlicensed frequencies in the optical wireless domain [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in such scenarios free-space optics (FSO) technologies present a viable solution while maintaining almost the same data throughput as the optical fiber and bridging the gap between the central office and BS. In recent years, numerous studies [9], [10], [11] have shown the possibilities of RoF transmission using FSO (denoted as RoFSO).…”
Section: Introductionmentioning
confidence: 99%